2014
DOI: 10.4306/pi.2014.11.4.481
|View full text |Cite
|
Sign up to set email alerts
|

Abelson Helper Integration Site-1 Gene Variants on Major Depressive Disorder and Bipolar Disorder

Abstract: ObjectiveThe present study aimed to explore whether 4 single nucleotide polymorphisms (SNPs) within the AHI1 gene could be associated with major depressive disorder (MD) and bipolar disorder (BD), and whether they could predict clinical outcomes in mood disorders.MethodsOne hundred and eighty-four (184) patients with MD, 170 patients with BD and 170 healthy controls were genotyped for 4 AHI1 SNPs (rs11154801, rs7750586, rs9647635 and rs9321501). Baseline and final clinical measures for MD patients were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…6). In 8 conclusion, the present study demonstrates that the mood-related protein AHI1 links the molecular circadian clock pathway to regulate TH expression.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…6). In 8 conclusion, the present study demonstrates that the mood-related protein AHI1 links the molecular circadian clock pathway to regulate TH expression.…”
Section: Discussionsupporting
confidence: 56%
“…Mutations in AHI1 are identified as a frequent factor of an autosomal recessive Joubert syndrome that is characterized by abnormal neurodevelopment and mental disturbance (1)(2)(3). Moreover, many lines of evidence indicate the linkage between AHI1 and neuropsychiatric disorders, including schizophrenia (SCZ) (4-7), depression (8), and autism (9). In animal model, Ahi1 knockout (KO) mice exhibit typical depressive behaviors, sharing common neurological characters in human psychiatric disorders, accompanied by decreases of neurotransmitters such as dopamine (DA) and serotonin (5-HT) in various brain regions (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidences have shown that Abelson helper integrationsite-1 (Ahi1) mutation is associated with a series of psychiatric diseases [29,30]. In addition, our previous studies also demonstrated that Ahi1 KO causes depression-like behaviors in mice [31,21], suggesting Ahi1 can be effectively targeted to develop a depression model.…”
Section: Resultsmentioning
confidence: 99%
“…Studying Ahi1 expression levels in lymphoblasts from schizophrenia patients, we found reduced expression in patients with early onset of the disorder 13 , leading us to suggest that reduced Ahi1 levels may be associated with susceptibility to schizophrenia. Association of Ahi1 with autism 14 , 15 and bipolar disorder 16 has also been reported.…”
Section: Introductionmentioning
confidence: 88%